Proactive monitoring system for wireless LAN device / Siti Rahayu Abdul Aziz, Noorhayati Mohamed Noor and Mohd Izani Mohamed Rawi - Abdul Aziz, Siti Rahayu; Mohamed Noor, Noorhayati; Mohamed Rawi, Mohd Izani (Research Management Institute (RMI), 2010)
Instant messaging(IM) is a real-time communication medium between two or more people. Users can exchange messages privately or involve in group conversations. Today, IM does not only allow text messages, it can also send images and audio and video conversation. Although it is deemed as a social tool, it is not restricted for communication between people. Besides people, Software can be also involved in IM conversation, this kind of software is called IM bot. IM bot is being used to provide user with weather, stock exchange and local news. However, the use of IM bot type software in system administration field is not much studied and it is also not much available. The goal of this project is to develop an IM bot to provide system administrator with remote machine status and information. A daemon type software is developed to create the machine presence on the IM network and allows system administrator to interact with the machine as the same service provided by Telnet and SSH. Furthermore, IM messages and presence information is used to relay system status and information to the system administrator. With the real-time nature of IM, this project can benefit system administrator with real-time system status and proactive notification messages. In addition, the contact list of IM, provides system administrator with the inventory of the machines they maintain.